2012
DOI: 10.1038/mt.2012.101
|View full text |Cite
|
Sign up to set email alerts
|

MyD88 Signaling in B Cells Regulates the Production of Th1-dependent Antibodies to AAV

Abstract: The administration of recombinant adeno-associated viral vectors (rAAV) for gene transfer induces strong humoral responses through mechanisms that remain incompletely characterized. To investigate the links between innate and adaptive immune responses to the vector, rAAVs were injected intravenously into mice deficient in cell-intrinsic components of innate responses (Toll-like receptors (TLRs), type-1 interferon (IFN) or inflammasome signaling molecules) and AAV-specific antibodies were measured. Of all molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 44 publications
(69 reference statements)
4
49
0
Order By: Relevance
“…As opposed to the initial findings, contradictory data in the literature suggest an incomplete role for TLR9 signaling or a function for MyD88 but not TLR9 in shaping antibody responses [18,20,22]. As a whole, our data agree with the latter conclusions.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…As opposed to the initial findings, contradictory data in the literature suggest an incomplete role for TLR9 signaling or a function for MyD88 but not TLR9 in shaping antibody responses [18,20,22]. As a whole, our data agree with the latter conclusions.…”
Section: Discussionsupporting
confidence: 84%
“…Others have previously reported that B cell-intrinsic MyD88 signaling may be required for the induction of IFN-γ-producing CD4 + T cells and subsequent formation of Th1-associated IgG2c antibody responses [22,28,29]. To verify this, we adoptively transferred WT B cells into MyD88 −/− mice 1 day prior to vector administration.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…However, it has been reported that in murine and human plasmacytoid dendritic cells in vitro, the AAV vector interacts with the innate immune system through the Toll-like receptor (TLR)9/MyD88 and type I interferon cascade [38,39]. AAV vectors also trigger nuclear factor kB-dependent production of cytokine and chemokine release in mouse liver, and MyD88 signaling in B cells also seems to control the production of capsid-specific T helper 1 antibody responses [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect on antibody formation overall is modest, as antibodies form even in TLR9 knockout mice [37]. IgG2a formation (the Th1-dependent murine equivalent of human IgG1) is dependent on intrinsic MyD88 in B cells [37, 39]. Antibodies that form against FIX upon AAV gene transfer in mouse and dog models, however, primarily reflect class-switch to Th2-dependent immunoglobulin (IgG1 in the mouse, equivalent to human IgG4).…”
Section: Multiple Factors Impact the Risk Of Immune Responses To Tmentioning
confidence: 99%